2001
DOI: 10.1038/sj.ejhg.5200723
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the two more frequent HFE mutations (C282Y and H63D): significant different allelic frequencies between the North and South of Portugal

Abstract: An earlier study of reference values of iron parameters in Portugal showed significant differences between populations from northern and southern villages. This study addresses the question of the geographical distribution in Portugal of the two main mutations (C282Y and H63D) of the hereditary hemochromatosis gene, HFE. For that purpose, a stratified sample of 640 anonymous dried blood spot samples was randomly selected from the major regions of Portugal: North, Center, Lisbon and the Tagus Valley, Alentejo a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 33 publications
3
25
0
1
Order By: Relevance
“…The allelic frequencies found for C282Y and H63D mutations in this study resemble the values obtained by Cardoso et al (2001) in a southern Portugal population and are in conformity with the distribution pattern found for southern European populations . It has been suggested that thalassemia-affected Italians had a lower HFE prevalence than the general Italian population .…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…The allelic frequencies found for C282Y and H63D mutations in this study resemble the values obtained by Cardoso et al (2001) in a southern Portugal population and are in conformity with the distribution pattern found for southern European populations . It has been suggested that thalassemia-affected Italians had a lower HFE prevalence than the general Italian population .…”
Section: Discussionsupporting
confidence: 73%
“…Nevertheless, all mutations studied had a higher frequency in controls. These frequencies were also compared with those found in a previous study by Cardoso et al (2001) regarding random controls of southern Portugal origin. Again, no statistically significant difference was found among these three groups.…”
Section: Hfe Allelic Frequencies and Genotypesmentioning
confidence: 93%
See 3 more Smart Citations